Insights into the pathogenicity of Penicillium marneffei - Cooper Jr. C.R. (2014)
Penicillium marneffei is a significant pathogen of AIDS patients in Southeast Asia. This fungus is unique in that it is the only dimorphic member of the genus. Pathogenesis of P marneffei requires the saprobic mold form to undergo a morphological change upon tissue invasion. The in vivo form of this fungus reproduces as a fission yeast that capably evades the host immune system. The processes that control these morphological changes, better termed as phase transition, can be replicated in vitro by incubation of the mold form at 37°C. The unidentified molecular mechanisms regulating phase transition in this fungus are now being uncovered using modern methodologies and novel strategies. A better comprehension of these underlying regulatory pathways will provide insight into eukaryotic cellular development as well as the potential factors responsible for infections caused by P. marneffei and other fungi. Such knowledge may lead to better chemotherapeutic interventions of fungal diseases. © 2008 Future Medicine Ltd.